2017
DOI: 10.3906/vet-1701-50
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the isolation and inhibition abilities ofselective media used for Brucella spp. Isolation

Abstract: The aim of this study was to compare and contrast the isolation ability of selective media developed for Brucella spp. isolation and their inhibition ability against contaminant microorganisms. Fifty-one field strains biotyped from abortion case samples and 25 Brucella spp. negative organ samples were used. Strain suspensions and organ suspensions were prepared separately. The turbidity of the strain suspensions was measured via spectrophotometer. The bacterial density of the strain suspensions was prepared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
3
3
0
3
Order By: Relevance
“…Since this can influence the accuracy of results in natural hosts, CM should be modified, as has been done with FM for use in sheep ( 33 ). Overall, the different degrees of inhibition observed for B. melitensis , B. abortus , and B. ovis strains were in line with previous studies with FM ( 15 , 17 , 19 , 34 ) or CM ( 35 ). All of these findings highlight the importance of medium composition when isolating a particular Brucella strain, even within the same species.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since this can influence the accuracy of results in natural hosts, CM should be modified, as has been done with FM for use in sheep ( 33 ). Overall, the different degrees of inhibition observed for B. melitensis , B. abortus , and B. ovis strains were in line with previous studies with FM ( 15 , 17 , 19 , 34 ) or CM ( 35 ). All of these findings highlight the importance of medium composition when isolating a particular Brucella strain, even within the same species.…”
Section: Discussionsupporting
confidence: 90%
“…A validation experiment using a total of 1,789 sheep samples revealed that BSM selectivity matched that of CM, successfully inhibiting both fungal and bacterial contaminants, in agreement with previous reports ( 17 , 19 , 35 38 ). Although medium formulation is a key factor for the maximum isolation of Brucella from veterinary samples, other strategies—such as clean sampling and tracing the cultures on a daily basis ( 35 ), external disinfection of organ/lymph node samples, or the use of two combined culture media ( 1 )—are also recommended practices.…”
Section: Discussionsupporting
confidence: 89%
“…Alton et al (1988) suggested passaging Brucella suspect colonies before the contaminants spread on the media's surface and they also recommended checking them three days after the incubation. However, contaminants might cover the surface of the medium completely earlier than the end of 3 days (Karagul and Ikiz 2017). In this study, it was possible to recognize the Brucella colonies on F+ER for some samples at the end of the second day of incubation.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, enhancing the growth of Brucella colonies as, it is in this study, might overcome this difficulty. Karagul and Ikiz (2017) stated that although a medium in their study had the lowest inhibition ability; it did not have the lowest isolation rate. This fact might be interpreted as the positive effect of the erythritol component it included.…”
Section: Discussionmentioning
confidence: 87%
“…In this gold standard, focusing on viable bacteria is very important. However, the decline of isolation sensitivity is a possible result because of the contaminant organisms in the samples (11). In such samples, the rate of the diagnosis of infected animals can be increased by PCR techniques through detecting the DNA from dead bacteria cells (8).…”
Section: Praca Oryginalnamentioning
confidence: 99%